Photoinduced C-C reactions on insulators toward photolithography of graphene nanoarchitectures - Palma, Carlos-Andres; Diller, Katharina; Berger, Reinhard; Welle, Alexander; Bjork, Jonas; Cabellos, Jose Luis; Mowbray, Duncan J.; Papageorgiou, Anthoula C.; Ivleva, Natalia P.; Matich, Sonja; Margapoti, Emanuela; Niessner, Reinhard; et al. (Journal of the American Chemical Society, 2014)
On-surface chemistry for atomically precise sp2 macromolecules requires top-down lithographic methods on insulating surfaces in order to pattern the long-range complex architectures needed by the semiconductor industry. Here, we fabricate sp2-carbon nanometer-thin films on insulators and under ultrahigh vacuum (UHV) conditions from photocoupled brominated precursors. We reveal that covalent coupling is initiated by C-Br bond cleavage through photon energies exceeding 4.4 eV, as monitored by laser desorption ionization (LDI) mass spectrometry (MS) and X-ray photoelectron spectroscopy (XPS). Density functional theory (DFT) gives insight into the mechanisms of C-Br scission and C-C coupling processes. Further, unreacted material can be sublimed and the coupled sp2-carbon precursors can be graphitized by e-beam treatment at 500 °C, demonstrating promising applications in photolithography of graphene nanoarchitectures. Our results present UV-induced reactions on insulators for the formation of all sp 2-carbon architectures, thereby converging top-down lithography and bottom-up on-surface chemistry into technology. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20